Optimization of Heat Transfer Performance Using Response Surface Methodology-Central Composite Design (RSM-CCD) for Nano-Coolant (Al2O3+EG/W) in Electric Vehicle Battery - Amri Abdulah; Dede Ardi Rajab; Iman Nurshahid; Sukarman; Khoirudin; Muhamad Taufik Ulhakim (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2024)
The presence of electric vehicles (EVs) must be supported by batteries that have good-quality energy storage. Battery power is critical to the development of electric cars. Temperature affects battery strength, so operating within the optimum temperature range must be ensured. During the charge and discharge processes, the electrochemical reaction generates hot energy, causing an increase in battery temperature. In this research, the solution to the problem is to make a cooling system with a mini channel cold plate and Al2O3 1%vol+EG/W (50:50) nano coolant. Optimization of heat transfer enhancement using Response Surface Methodology-Central Composite Design (RSM-CCD) and experimental tests with various flow rate variations. The research findings revealed that the RSM-CCD results and the outcomes of studies employing test equipment agreed that the highest cooling fluid flow rate was the most optimal condition, the highest T2 temperature drop of 17.63% occurred at a flow rate of 1.7 LPM, and the lowest T2 temperature was 13.13% at a flow rate of 1 LPM.